Efektivitas Pertukaran Informasi Otomatis Dalam Menangkal Penghindaran Pajak - Chairil Anwar Pohan; Notika Rahmi; Putri Ayu Lestari (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
Global financial transactions are one of the most important issues in the world of taxation. These global financial transactions are often one of the ways for taxpayers to do tax evasion and evasion. As a solution to the problem, the government established the Automatic Exchange of Information (AEoI) which is a system that supports the exchange of taxpayer account information between countries at a certain time periodically, systematically, and continuously from the country of income source or place of storing wealth, to the resident country of the taxpayer. This study was conducted with the aim of analyzing the effectiveness of AEoI in preventing tax evasion. This study used a qualitative research method with a descriptive approach, data collection was obtained through interviews, observation and documentation. The research subject is the Directorate General of Taxes (DGT). The results show that from the perspective of effectiveness, the role of AEoI in preventing tax evasion has so far been quite effective because of the big data from AEoI, but there are still weaknesses of AEoI in the completeness of the incomplete or unequal NPWP system data from partner countries so that DGT meets difficulty in tracing it because there is no control feature on the system in matching the NPWP. In addition, the readiness of the internal system in each country and the different capacities of each country related to the completeness of data from partner countries can affect the quality of data information which can become an obstacle in the exchange of information.